Integration of family planning services into HIV care clinics: Results one year after a cluster randomized controlled trial in Kenya. - Craig R Cohen; Daniel Grossman; Maricianah Onono; Cinthia Blat; Sara J Newmann; Rachel L Burger; Starley B Shade; Norah Bett; Elizabeth A Bukusi (PLoS ONE, 2017)
OBJECTIVES:To determine if integration of family planning (FP) and HIV services led to increased use of more effective contraception (i.e. hormonal and permanent methods, and intrauterine devices) and decreased pregnancy rates. DESIGN:Cohort analysis following cluster randomized trial, when the Kenya Ministry of Health led integration of the remaining control (delayed integration) sites and oversaw integrated services at the original intervention (early integration) sites. SETTING:Eighteen health facilities in Kenya. SUBJECTS:Women aged 18-45 receiving care: 5682 encounters at baseline, and 11628 encounters during the fourth quarter of year 2. INTERVENTION:"One-stop shop" approach to integrating FP and HIV services. MAIN OUTCOME MEASURES:Use of more effective contraceptive methods and incident pregnancy across two years of follow-up. RESULTS:Following integration of FP and HIV services at the six delayed integration clinics, use of more effective contraception increased from 31.7% to 44.2% of encounters (+12.5%; Prevalence ratio (PR) = 1.39 (1.19-1.63). Among the twelve early integration sites, the proportion of encounters at which women used more effective contraceptive methods was sustained from the end of the first to the second year of follow-up (37.5% vs. 37.0%). Pregnancy incidence including all 18 integrated sites in year two declined in comparison to the control arm in year one (rate ratio: 0.72; 95% CI 0.60-0.87). CONCLUSIONS:Integration of FP services into HIV clinics led to a sustained increase in the use of more effective contraceptives and decrease in pregnancy incidence 24 months following implementation of the integrated service model. TRIAL REGISTRATION:ClinicalTrials.gov NCT01001507.